2018
DOI: 10.1371/journal.pone.0202821
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity of Staphylococcus aureus biofilm under combined exposure of glutaraldehyde, near-infrared light, and 405-nm laser

Abstract: Healthcare-associated infections have increasingly become problematic in the endoscopic procedures resulting in several severe diseases such as carbapenem-resistant Enterobacteriaceae (CRE)-related infections, pneumonia, and bacteremia. Especially, some bacterial strains are resistant to traditional antimicrobials. Therefore, the necessity of developing new antibiotics or management to deal with bacterial infections has been increasing. The current study combined a low concentration of glutaraldehyde (GTA) wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 56 publications
(73 reference statements)
0
8
0
3
Order By: Relevance
“…Indeed, the experiments showed that the linked GA alone contributed, though slightly, to decrease the biofilm formation on the surface (up to 31.0%) (Figure 2A,C), with a mechanism that did not affect cell viability. A weak GA effect on Bacillus cereus , Pseudomonas fluorescens , Staphylococcus aureus , and E. coli biofilm formation was previously reported in the literature [74,75,76,77]. However, these studies highlighted that GA had a significant effect on biofilm removal, inducing sloughing events, only under long-term exposure [75].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Indeed, the experiments showed that the linked GA alone contributed, though slightly, to decrease the biofilm formation on the surface (up to 31.0%) (Figure 2A,C), with a mechanism that did not affect cell viability. A weak GA effect on Bacillus cereus , Pseudomonas fluorescens , Staphylococcus aureus , and E. coli biofilm formation was previously reported in the literature [74,75,76,77]. However, these studies highlighted that GA had a significant effect on biofilm removal, inducing sloughing events, only under long-term exposure [75].…”
Section: Discussionmentioning
confidence: 93%
“…Indeed, GA forms methylene bridges, which may play a part in subsequent reactions including cross-linking with another protein chain in the cells. This leads to the removal of water from the biofilm followed by a dehydration effect [77,78]. In addition, it is reported that GA causes the deformation of alpha-helix structures in proteins on the outer cellular layers [79], which may include some proteins important for bacterial adhesion and biofilm formation.…”
Section: Discussionmentioning
confidence: 99%
“…The implementation of the microfluidic method can aid in monitoring the mono- and dual-species biofilm formation between S. aureus and C. albicans in real-time. Besides, an optical treatment for the bacterial biofilms using 405-nm laser light has been widely deployed to evaluate the antibacterial effect on bacterial biofilms in vitro 37 ; however, the research on the 405-nm laser light for dual-species biofilm eradication with the assistance of the microfluidic platform under hydrodynamic conditions is lacking. Therefore, the current study intended to develop a versatile, yet simple microfluidic platform to investigate the formation of mono- and dual-species biofilms of S. aureus and C. albicans in real-time.…”
Section: Introductionmentioning
confidence: 99%
“…Os efeitos antibacterianos da luz IV em suspensões de Salmonella enterica serovar Typhimurium e Escherichia coli 13 e em biofilmes in vivo 14 e in vitro 15,16 de Staphylococcus aureus foram estudados por alguns pesquisadores. Por meio de efeitos térmicos e de fotodisrupção, a LBI promove ruptura da parede celular bacteriana e acúmulo de proteína desnaturada no citoplasma bacteriano, levando, assim, a danos letais e subletais à célula 17,18 .…”
Section: Introductionunclassified
“…Assim como no presente estudo, os autores não observaram redução da viabilidade bacteriana, após uso da laserterapia. Tran et al (2018)16 observaram uma redução da viabilidade bacteriana em biofilmes de S. aureus quando a combinação laser IV (780 nm -1060 nm) e laser azul (405 nm) foi utilizada, porém não observaram essa redução quando o laser IV foi utilizado sozinho. Esses resultados corroboram os encontrados na presente pesquisa, em que não observamos efeito antimicrobiano do laser IV.…”
unclassified